2001
DOI: 10.1183/09031936.01.00034601
|View full text |Cite
|
Sign up to set email alerts
|

High morbidity and mortality in cystic fibrosis patients compound heterozygous for 3905insT and ΔF508

Abstract: High morbidity and mortality in cystic fibrosis patients compound heterozygous for 3905insT and DF508. A. Schibler, I. Bolt, S. Gallati, M.H. Schöni, R. Kraemer. #ERS Journals Ltd 2001. ABSTRACT: Genotype-phenotype association in cystic fibrosis (CF) is difficult because of heterogeneous disease expression. The genotype-phenotype correlation for the 3905insT mutation in comparison to DF508 was studied here.Thirty CF patients compound heterozygous for 3905insT were compared to clinical presentation of matched p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…Nevertheless, the variability of pulmonary function at time of diagnosis in infants [21] and children [84-86] has been found to be partially related to the genotype. In comparison to the inframe homozygotes ΔF508(2) and nonsense R553X/ΔF compound heterozygotes, patients carrying one frameshift mutation 3905insT have a poorer prognosis with respect to the onset of pulmonary disease, progression of lung function, and mortality [87]. Schaedel et al used FEV 1 % normal predicted to demonstrate a slower rate of decline in patients with missense mutations compared with ΔF508(2) homozygotes [86], and Cory et al used LMM analysis to show a slower rate of pulmonary function decline in some patients with non-ΔF508 mutations [51].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the variability of pulmonary function at time of diagnosis in infants [21] and children [84-86] has been found to be partially related to the genotype. In comparison to the inframe homozygotes ΔF508(2) and nonsense R553X/ΔF compound heterozygotes, patients carrying one frameshift mutation 3905insT have a poorer prognosis with respect to the onset of pulmonary disease, progression of lung function, and mortality [87]. Schaedel et al used FEV 1 % normal predicted to demonstrate a slower rate of decline in patients with missense mutations compared with ΔF508(2) homozygotes [86], and Cory et al used LMM analysis to show a slower rate of pulmonary function decline in some patients with non-ΔF508 mutations [51].…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that patients heterozygous for 3905insT have similar high morbidity and mortality to patients homozygous for Δ F508, including underweight and poor growth (51) .…”
Section: (3 Months To 6 Years)mentioning
confidence: 98%
“…[9][10][11][12] The mutation is characterized by the introduction of a PTC in exon 20 of the CFTR gene. PTCs can be recognized by the so-called NMD, which degrades transcripts bearing such PTCs thereby preventing the formation of a truncated protein.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies based on clinical parameters have shown that the 3905insT mutation is associated with a severe phenotype. [9][10][11][12] The insertion of an additional thymidine in exon 20 leads to a premature termination codon (PTC) in the same exon. It is well known that PTCs can activate the nonsense-mediated mRNA decay (NMD).…”
Section: Introductionmentioning
confidence: 99%